2015
DOI: 10.4314/ejhs.v25i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between emotional intelligence and organizational citizenship behavior in critical and emergency nurses in south east of Iran

Abstract: BACKGROUND: Several factors including emotional intelligence affect the efficiency of people. It seems that organizational behavior of each person is strongly influenced by emotional intelligence. Therefore, the present study is aimed to examine the relationship between emotional intelligence and organizational citizenship behavior in critical and emergency nurses in teaching hospitals supervised by Kerman Medical University in Southeast of Iran. METHODS: This study employed a descriptive cross sectional desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…These results remind us that emotional intelligence can be learned and developed at any marital status, education level, working experience age, and gender. However, several studies showed that there was significant relation between emotional intelligence and nurses' perception of job performance with the factors [ 31 , 32 ]. It can be said that, with increasing age and work experience and ability to adapt with changes, personal and social problem solving also increase.…”
Section: Discussionmentioning
confidence: 99%
“…These results remind us that emotional intelligence can be learned and developed at any marital status, education level, working experience age, and gender. However, several studies showed that there was significant relation between emotional intelligence and nurses' perception of job performance with the factors [ 31 , 32 ]. It can be said that, with increasing age and work experience and ability to adapt with changes, personal and social problem solving also increase.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it requires an environment which cultivates team building and collaboration. For example, Tofighi et al (Tofighi, Tirgari, Fooladvandi, Rasouli, & Jalali, 2015) noted that the four components of EI (awareness of the self, awareness of others, management of self and management of relationships with others) (Goleman et al, 2002) work together to increase employee behavior geared towards organizational benefit, without a desire for compensation. Zhu et al noted that EI, when found in a work environment that prioritizes fairness, increases nurses' engagement in the workplace (Zhu et al, 2015).…”
Section: Ei and Workplace Environmentmentioning
confidence: 99%
“…Training, especially at the level of emotional intelligence, translates into benefits for nurses, even on an individual basis, as their own health status (study E). The literature establishes benefits of post-graduate training (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)21) and educational interventions (23) to the level of emotional intelligence of nurses.…”
Section: Discussionmentioning
confidence: 99%